Faktor-Faktor yang Memperngaruhi Eksistensi Kesenian Reog Grup Krido Budoyo di Desa Bangun Jaya Kecamatan Tambusai Utara Kabupaten Rokan Hulu Provinsi Riau - Rima Ahmad Mulyani; Laila Fitriah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2026)
This study ains to determine the factors that influence the existence of Reog art of the Krido Budoyo Group in Bangun Jaya Village, North Tambusai District, Rokan Hulu Regency, Riau Province. The theory used in this research is the Dagun Save M. theory (in Gracia Destari Mujianto and Eko Raharjo 2019:129) with indicators of Work Activity, Having Facts, and Efforts to Maintain Its Existence. The method used in this study is descriptive analysis using qualitative data, with data collection techniques, namely observation, interview and documentation techniques. The subjects in this study were 10 people. The results of the findings of this study were (i) in terms of the indicators of the work activities of Reog Krido Budoyo ini Bangun Jaya Village received invitations to events, and still widely known by the people of Rokan Hulu Regency, (ii) in terms of indicators of having facts, Reog Krido Budoyo in Bangun Jaya Village has a rhythm pattern in the Reog dance music used, group organizational stucture, customes used, and performances by the Reog Group Krido Budoyo, (iii) viewed from the business aspect in Bangun Jaya Village, the training studio is open to the public so that the existence of Reog Krido Budoyo continues of develop and survive.